Study of Maca (Lepidium meyenii Walp.), Andean crop with therapeutic properties - Sifuentes-Penagos, Gabriel (2015)
The maca is a native product of the Central Andes of Peru, it is resistant to hail, to frost and to prolonged droughts. It is cultivated from the Inca period in altitudes between 3800 - 4500 meters above sea level. This herbaceous plant, has not only a high nutritional value, but it is also valued for its medicinal role. Among the chemical components of this andean crop that have been related with therapeutic actions the increasing fertility and the energy levels, the antioxidant actions, the improving sexual desire and the growth rate. There are glucosinolates, sterols, fatty acids (macaene) and their corresponding amides (macamides), alkaloids (lepidilines A and B, macaridine) and polyphenols. This article presents a compilation of the researches that has been performed on the therapeutic properties of maca and its compounds responsible of them